Eclectic façade / Fiona Wong E Chiong - Wong, Fiona E Chiong (Faculty of Art and Design, 2021)
The artwork titled Eclectic Façade portrays four fanlite windows of different shophouse façades that were built in the early twentieth century British Malaya. This type of windows were common in two- or three-storey shophouses located in many major towns (many now cities) all over the country, in East and West Malaysia, especially in the Peninsular. Known as the transitional type of shophouse, these built structures began to experience transformation on their appearances as the builders, artisans and owners started to be creative and expressive with different styles of design and colours. Influenced by the then European architectural and stylistic trends, the shophouse began to witness an evolutionary change in its façade from a plain structure and unadorned exterior into an eclectic surface depicting European influences of Greek columns and pilasters, Venetian windows and vents, Renaissance motifs on cornices and stucco reliefs; the window shutters are made of local wood and are sometimes carved in Malay-styled motif; Chinese-characters or letterings and sometimes symbolic images may appear on the signages or as plastered reliefs.